The Epic in World Culture - Thornton, Niamh (Imagofagia, 2021)
Sobre Burgoyne, Robert (Coord.) The Epic in World Culture. New York/London, AFI Film Readers/Routledge, 2011, 391 pp., ISBN978-0-415-99018-9. Palabras clave: reseña, Robert Burgoyne, The Epic in World Culture